An Overview of Medical Students’ Psychological in The Process of Distance Learning on Pandemic COVID-19 - Tubarad, Gladys D T; Wiratmoko, Mirsyam Ratri; Aulia, Silmi Nur; Prameswari, Seline Calysta; Pramana, Satya (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: The spread of COVID-19 in Indonesia in June 2020 does not yet show signs of a decrease. Therefore, Indonesia's Ministry of Education and Culture takes preventive transmission in the educational environment by making the decision letter with four ministers agreeing that learning in higher education of the academic year 2020/2021 in all zones shall be held online. Online learning is a learning system that does not need face to face directly but uses a platform that can help the process of distance learning. The burden of learning materials and academic demands of medical students can cause students anxiety, especially in the pandemic COVID-19. Purposes: to determine an overview of the medical students' psychological in distance learning during the pandemic COVID-19. Methods: This is a cross-sectional study using descriptive quantitative analysis. The data used primary data through Depression Anxiety and Stress Scale (DASS-21) questionnaire. Results: The results of the study showed that the highest percentage is at mild anxiety about 47.3%, mild stress level with 7.8%, and mild depression that 13.2%. Factors that can lead to psychological disorders in medical students, the demands of learning, and a sense of worry excessive about the process and the results. Conclusions: Factors that lead to anxiety, stress, and depression in medical students when implementing distance learning can be different for each individual.